2018
DOI: 10.1101/338434
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Novel Wolbachia strains in Anopheles malaria vectors from Sub-Saharan Africa

Abstract: Anopheles (An.) mosquitoes contain bacteria that can influence Plasmodium parasites. Wolbachia, a common insect endosymbiont, has historically been considered absent from Anopheles but has recently been found in An. gambiae populations. Here, we assessed a range of Anopheles species from five malaria-endemic countries for Wolbachia and Plasmodium infection. Strikingly, we found Wolbachia infections in An. coluzzii, An. gambiae s.s, An. arabiensis, An. moucheti and An. species ‘A’ increasing the number of Anoph… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 83 publications
(125 reference statements)
1
14
0
2
Order By: Relevance
“…In arthropods, Wolbachia is broadly spread, including among Culex and Aedes mosquitoes. Conversely, it was believed that in the genus Anopheles, Wolbachia infections were mainly limited to species within the gambiae complex 23,25 , and few other species 22 . Several hypotheses can be put forward to explain this.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In arthropods, Wolbachia is broadly spread, including among Culex and Aedes mosquitoes. Conversely, it was believed that in the genus Anopheles, Wolbachia infections were mainly limited to species within the gambiae complex 23,25 , and few other species 22 . Several hypotheses can be put forward to explain this.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, only one stable transfected Wolbachia colony has been described in Anopheles stephensi 18 . Therefore, data on the use Wolbachia for Anopheles control remain scarce and mainly concern experimental studies in laboratory conditions 18,19 , due to technical (i.e., egg microinjection) and biological (i.e., competitive exclusion with the bacterium Asaia) difficulties to carry out transinfections in Anopheles , despite multiple assays 2022 For long time, it was believed that Wolbachia was absent in natural populations of Anopheles 20 . However, in the last few years, three studies reported that An.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…albopictus populations in Madagascar (including resident Wolbachia strains) concluded that the environment was a factor in the overall microbiota composition and diversity 68 . It has also recently been shown that there is no evidence for Wolbachia-Asaia co-infections in a wide range of Anopheles species and the environment likely influences Asaia prevalence and density in wild mosquito populations 69 .…”
Section: Discussionunclassified
“…darlingi ), which has led to the previous believe that Wolbachia were unable to infect Anopheles species until their very recent discovery in natural populations of Anopheles gambiae and Anopheles coluzzii in Burkina Faso [21, 65] and in Mali (Gomes et al 2017). More recently Ayala et al [66] and Jeffries et al [67] have revealed that native Wolbachia infections was wider than expected among natural anopheline populations with at least 16 species naturally infected (Table 4). Furthermore, Ayala et al [66] revealed a large diversity of Wolbachia strains in wild anopheline populations, which offers an unexpected opportunity to discover suitable phenotypes to suppress Plasmodium transmission and/or to manipulate Anopheles reproduction and reduces the malaria burden in Africa [66].…”
Section: Main Textmentioning
confidence: 97%